Предмет: Алгебра,
автор: yeahor
спростіть вираз -(x²-2)(x-2)-5(x+1)²=2(3-x²)+7
Ответы
Автор ответа:
0
Відповідь:
-х³-х²-8х-22=0
Пояснення:
-(х²-2)(х-2)-5(х+1)² = 2(3-х²)+7
-(х³-2х²-2х+4)-5(х²+2х+1) = 6-2х²+7
-х³+2х²+2х-4-5х²-10х-5 = 6-2х²+7
-х³+2х²+2х-4-5х²-10х-5-6+2х²-7 = 0
-х³-х²-8х-22 = 0
Якщо вираз ×(-1) у нас вийде:
х³+х²+8х+22 = 0
Похожие вопросы
Предмет: Окружающий мир,
автор: Аноним
Предмет: Английский язык,
автор: iLinkov
Предмет: Русский язык,
автор: 1234567890237
Предмет: Алгебра,
автор: masadropd1
Предмет: Русский язык,
автор: okorokova1